1992
DOI: 10.1016/0735-1097(92)90193-q
|View full text |Cite
|
Sign up to set email alerts
|

Serial analysis of regional left ventricular wall motion by two-dimensional echocardiography in patients with coronary artery enlargement after Kawasaki disease

Abstract: These early changes are most likely secondary to associated myocarditis rather than coronary artery abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Myocarditis is a well-recognized component of KD, with left ventricular systolic dysfunction occurring in 50-70% of patients during the acute stage [1][2][3][4][5][6][7][8][9][10]. Abnormalities of left ventricular contractility and systolic function have been documented to resolve within 12 months of onset of KD, with rapid improvement after the administration of intravenous immunoglobulin (IVIG) [1][2][3].…”
Section: Introductionmentioning
confidence: 97%
“…Myocarditis is a well-recognized component of KD, with left ventricular systolic dysfunction occurring in 50-70% of patients during the acute stage [1][2][3][4][5][6][7][8][9][10]. Abnormalities of left ventricular contractility and systolic function have been documented to resolve within 12 months of onset of KD, with rapid improvement after the administration of intravenous immunoglobulin (IVIG) [1][2][3].…”
Section: Introductionmentioning
confidence: 97%
“…KD is now the leading source of acquired heart disease in children [17,28]. Prior studies have clearly identified the presence of myocardial involvement in the acute phase of KD, specifically myocarditis that has been shown to be associated with subclinical and clinical left ventricular dysfunction [2,9,11,12,14,16,18,27]. Standard therapy for patients with acute KD is treatment with intravenous immune globulin (IVIG) which reduces the risk of CAL from 25 to 5 % [19].…”
Section: Introductionmentioning
confidence: 98%